Coaching Nenek ASI dalam Penerapan Massage Effleurage menggunakan Jitu Oil dengan Terapi Murottal Al-Qur'an untuk Mendukung Pemberian ASI Eksklusif - Ningsih, Dewi Andariya; Sumartini, Rina; Sakinah, Innama (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Choosing Breastfeeding Grandmothers is an effort to maximize the role of grandmothers in making exclusive breastfeeding a success. So far, grandmothers are the people in the family who are considered more capable and have a lot of experience, especially in caring for babies. This is the basis for this service in order to maximize the role of grandmothers in helping breastfeeding mothers provide good nutrition to their babies. Objectives There is an increase in knowledge, changing attitudes and behavior of breastfeeding grandmothers in the application of effleurage massage using Jitu oil to support exclusive breastfeeding and interaction and sharing of information through coaching breastfeeding grandmothers in the application of Effleurage Massage using Jitu Oil to support exclusive breastfeeding. Method Training implementation time January 26, 2024, mentoring implementation January 27 - February 26, 2024. The location of the activity is at the Lamongan Arjasa Village Hall. Method using PAR (Participatory Action Research), Results: This activity was attended by 19 grandmothers and 19 breastfeeding mothers. At the time of Choosing 12 people had good knowledge, 4 had sufficient knowledge, and 3 people had less. At the time of post-mentoring, 14 people had good skills, 3 people had sufficient knowledge and 2 people had less. Conclusion: The Choosing and mentoring activities carried out can increase knowledge and improve the skills of Grandmothers in performing Massage Effluerage massage to help relax the body of breastfeeding mothers.